A Systematic Review of the Pros and Cons of Digital Pollution and its Impact on the Environment - Oo, KYAW Than; Jonah, KAZORA; Thin, MOH Moh Zaw (Journal of Sustainability and Environmental Management, 2023)
Digital technologies are becoming more important in our daily lives. Because of digital technology, our carbon footprint has significantly increased and caused ecological consequences. As gadgets get smaller and have more internal components, there is more trashes produced during manufacture. By 2023, more than 70% of the world's population will own a mobile phone. From the start of the Covid-19 pandemic and the numerous ensuing lockdowns, there has been an exponential increase in the use of video transmission (streaming) all over the world. In fact, according to the International Energy Agency (IEA), watching an hour of video streaming on Netflix entails emissions of 36gCO2. Between 2020 and 2030, the overall amount of data transmission will increase fourteen times. Digital technologies can contribute up to 20% to net-zero energy, materials, and mobility reduction required by IEA by 2050. However, there aren't many summaries of the digital transformation of environmental sustainability. This review presents the implications of the digital world on environmental sustainability, including both beneficial and detrimental aspects. Some methods are based on the network and its energy consumption. The outcomes also show how changes in three key areas—waste management and handling, pollution prevention and control, and sustainable resource management—have preserved the environment. The footprints are also significantly smaller than previously predicted. While subscriptions and data traffic have continued to rise, the footprint of the ICT and E&M sectors has shrunk. As countless individuals are used to digital daily life, this study points out the challenges to govern this issue. This review also points out the potential and problems in this field, which tries to provide a vision for future research, based on the literature overview.